Види концептуальної моделі СППР - Верес, Олег; Верес, Юрій (Видавництво Львівської політехніки, 2013)
Description and classification of components of conceptual model of the decision support system is offered in the article. The analysis of going is conducted near the construction of conceptual model of the decision support system.
Keywords: класифікація; модель; концептуальна; децидент; СППР